Pursuing scale and quality in STI interventions with sex workers: initial results from Avahan India AIDS Initiative. Issue 5 (29th September 2006) - Steen, R; Mogasale, V; Wi, T; Singh, A K; Das, A; Daly, C; George, B; Neilsen, G; Loo, V; Dallabetta, G
Abstract : Background: Migration, population mobility, and sex work continue to drive sexually transmitted epidemics in India. Yet interventions targeting high incidence networks are rarely implemented at sufficient scale to have impact. India AIDS Initiative (Avahan), funded by the Bill and Melinda Gates Foundation, is scaling up interventions with sex workers (SWs) and other high risk populations in India's six highest HIV prevalence states. Methods: Avahan resources are channelled through state level partners (SLPs) to local level non-governmental organisations (NGOs) who organise outreach, community mobilisation, and dedicated clinics for SWs. These clinics provide services for sexually transmitted infections (STIs) including Condom Promotion, syndromic case management, regular check-ups, and treatment of asymptomatic infections. SWs take an active role in service delivery. STI capacity building support functions on three levels. A central capacity building team developed guidelines and standards, trains state level STI coordinators, monitors outcomes, and conducts operations research. Standards are documented in an Avahan-wide manual. State level STI coordinators train NGO clinic staff and conduct supervision of clinics based on these standards and related quality monitoring tools. Clinic and outreach staff report on indicators that guide additional capacity building inputs. Results: In 2 years, clinics with community outreach for SWs have been established in 274 settings covering 77 districts. Mapping and size estimation have identified 187 000 SWs. In a subset of four large states covered by six SLPs (183 000 estimated SWs, 65 districts), 128 326 (70%) of the SWs have been contacted through peer outreach and 74 265 (41%) have attended the clinic at least once. A total of 127 630 clinic visits have been reported, an increasing proportion for recommended routine check ups. Supervision and monitoring facilitate standardisation of services across sites. Conclusion: Targeted HIV/STI interventions can be brought to scale and standardised given adequate capacity building support. Intervention coverage, service utilisation, and quality are key parameters that should be monitored and progressively improved with active involvement of SWs themselves.